Proceedings 2006 IEEE International Conference on Robotics and Automation, 2006. ICRA 2006.
DOI: 10.1109/robot.2006.1642011
|View full text |Cite
|
Sign up to set email alerts
|

Range-only SLAM for robots operating cooperatively with sensor networks

Abstract: Abstract-A mobile robot we have developed is equipped with sensors to measure range to landmarks and can simultaneously localize itself as well as locate the landmarks. This modality is useful in those cases where environmental conditions preclude measurement of bearing (typically done optically) to landmarks. Here we extend the paradigm to consider the case where the landmarks (nodes of a sensor network) are able to measure range to each other. We show how the two capabilities are complimentary in being able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 20 publications
0
74
0
Order By: Relevance
“…However, signal strength measurements are often erratic and can be aected by slight changes in the environment. Alternately, xed ultrasound emitters and embedded receivers have also been used to measure range between nodes in a network [4,5,1]. Our system utilizes a new commercially available ranging radio system, the nanoLOC ranging system from Nanotron Technologies [6].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, signal strength measurements are often erratic and can be aected by slight changes in the environment. Alternately, xed ultrasound emitters and embedded receivers have also been used to measure range between nodes in a network [4,5,1]. Our system utilizes a new commercially available ranging radio system, the nanoLOC ranging system from Nanotron Technologies [6].…”
Section: Related Workmentioning
confidence: 99%
“…Here we focus on the problem of estimating the node positions of a sensor network given only range data between nodes in the network. Previous work have shown that, given sucient connectivity between the nodes in the network, it is possible to acquire an accurate estimate of the node positions [1,2]. However, existing strategies assume fairly simplistic scenarios, where the nodes operate within a large open area with little impedance to their measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has considered visual [1,2,3], range-only [4,5], and acoustic SLAM [6], as well as solutions based on multiple sensor modalities [7]. In [6], the authors propose a framework to simultaneously localizes the mobile robot and multiple sound sources using a microphone array on the robot.…”
Section: Introductionmentioning
confidence: 99%
“…However, sensors may have a limited angle of sensing range due to special applications, which are denoted as directional sensors. There are many kinds of directional sensors, such as video sensors [4,5], ultrasonic sensors [6] and infrared sensors [2]. The most familiar directional sensors are the video sensors widely used in wireless multimedia sensor networks (WMSNs).…”
Section: Introductionmentioning
confidence: 99%